Social stratification and human diet in the Eastern Zhou China: An isotopic view from the Central Plains. (December 2019) - Zhou, Ligang; Yang, Shugang; Han, Zhaohui; Sun, Lei; Garvie-Lok, Sandra J.
Abstract: Stable carbon and nitrogen isotope analysis of two nobles, twenty-four burial companions, thirty-nine rural commoners, and seventy-five urban individuals excavated from the Central Plains in northern China enables this first study of status differences in human diet during the highly stratified Eastern Zhou Dynasty. The results indicate that nobles had a millet-based diet, and ate substantially more animal protein than all the other individuals, confirming their reputation as "meat eaters". The burial companions (individuals buried along with nobles) were probably servants living with their masters in cities; they display similar dietary features to other urban commoners who ate limited animal protein and a certain amount of wheat, a non-preferred staple. Contemporary rural populations ate millet as their staple food and a similar amount of animal protein to urban people; no evidence of wheat consumption was found isotopically, suggesting that rural life was less affected than life in urban areas during this chaotic era. These isotopic data provide initial evidence for status patterning including a noble-commoner dietary dichotomy in staple foods, rural-urban dietary differences, and a similarity between the diets of burial companions and urban residents. These patterns provide a new window into life style and social stratification in Eastern Zhou China. Highlights: Human diet during the Eastern Zhou was greatly affected by social stratification. Nobles ate substantially more meat than other people, confirming their reputation as the "meat eaters". Rural people ate less wheat and similar amount of meant than urban people did. Rural life was less affected than the urban area during the Eastern Zhou. Burial companion of the nobles ate a similar diet as did urban people.